Implementasi Media Canva pada Pembelajaran Bahasa Indonesia Teks Negosiasi Kelas X SMA Negeri 11 Semarang - Hana Silma Hadana; Asep Purwo Yudi Utomo; Nurus Sa’adah; Titis Ardyasti (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
Technological developments have an impact on making interactive media in learning. Today’s learning media is more varied, especially Canva media. The purpose of this study was to find out the implementation of Canva media in Indonesian language learning in negotiating text material for class X SMA N 11 Semarang. This research also aims to make teachers more motivated in making learning media interesting, creative, and interactive. This type of research is qualitative using observation, interview, and documentation methods. This research was conducted in January 2023 at SMA Negeri 11 Semarang. The sources for this study were students in Class X SMA Negeri 11 Semarang. Existing data is in the form of behavior in implementing Canva media in learning Indonesian in negotiating text material. The analytical method used in this case is interactive analysis. The presentation of the results of data analysis in this article uses an informal method. The results of the implementation of Canva media in learning Indonesian in the negotiating text material for class X SMA N 11 Semarang went well, conducive, and interactive. There are several weaknesses that arise when learning takes place. However, the advantages of this implementation have more impact than disadvantages. Learning that is monotonous and makes students bored can be overcome with the Canva application as an interactive learning medium.